An IEEE 1149.x Embedded Test Coprocessor - José Manuel Martins Ferreira (2014)
This paper describes a microprogrammed architecture for an embedded coprocessor that is ableto control IEEE 1149.1 to IEEE 1149.7 test infrastructures, and explains how to expand the supportedtest command set. The coprocessor uses a fast simplex link (FSL) channel to interface a32-bit MicroBlaze CPU, but it can work with any microprocessor core that accepts this simpleFIFO-based interface method. The implementation cost (logic resource usage for a Xilinx Spartan6FPGA) and the performance data (operating frequency) are presented for a test command setcomprising two parts: 1) the full IEEE 1149.1 structural test operations; 2) a subset of IEEE 1149.7operations selected to illustrate the implementation of advanced scan formats.